Understanding pharmacology a physiologic approach - Grajeda-Higley, Leilani (Appleton & Lange, 2000)
The premise of the book is that there are three distinct body systems - the nervous system, the endocrine system and the immune system - and that each system has its own molecular language. The systems work together and communicate through this molecular language to maintain health. This text looks at drugs as chemicals that mimic these molecular languages. This concept, which the author calls the Master Systems Approach, is a unique, simplified way of teaching pharmacology that is not found in other texts